754 carlo vallardi (1886–1962). an assistant of luigi devoto deported to mauthausen concentration camp. (24th April 2018) - Riva, MA; Belingheri, M; Turato, M; Cesana, G
Abstract : Introduction: Carlo Vallardi, assistant of Luigi Devoto (1864–1936) at the 'Clinica del Lavoro' in Milan, is an often-forgotten figure in the history of Occupational Health. Methods: The historical investigation was conducted on documents belonging to the Ravelli Archive of the 'Fondazione Memoria della Deportazione' in Milan. Results: Vallardi was born in Milan on 2 March 1886; he belonged to a family of famous publishers. Graduated in Pavia in 1907, he began to attend as a volunteer at the Institute of Internal Medicine directed by Carlo Forlanini (1847–1918). After a short period of research in Berlin, Vallardi returned to Milan, where he began to attend the Clinica del Lavoro, focusing mainly on chronic phosphorus poisoning and lead intoxication. In 1913, he started to work at the Fatebenefratelli Hospital in Milan. During the years of World War I, he was called up as a medical officer at the front, where he conducted scientific studies on amoebic dysentery among troops. After the end of the war, he returned to Milan and continued his clinical work at the Fatebenefratelli Hospital. He openly contested Fascism. Arrested for his political ideas in March 1943, he was first transferred to the deportation camp in Fossoli, and then to the Mauthausen-Gusen concentration camp. Thanks to his knowledge of German language and his clinical skills, he was assigned to the camp hospital. As a result of this position, he managed to save the life of several prisoners, and avoid the gas chamber. Vallardi died in his hometown on 17 December 1962. Conclusion: The passion for the clinic and for scientific research – especially in occupational toxicology – and the acts of heroism in the years of deportation make Carlo Vallardi a model and an example to follow.